Analisis Pengaruh Inflasi, Kurs Dollar, dan Suku Bunga Terhadap Ekspor Hasil Perikanan di Provinsi Bali - Rahayu, Tika Aryasih; Budhiasa, I Gede Sujana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 12, Desember 2016 (pp. 1347-1585), 2017)
Exports of fishery products is one of the largest sub-sector that contributes to the total export value of Bali Province. This study aimed to analyze the effect of inflation, interest rates, and the exchange rate on exports of fishery products fishery in the province of Bali, to analyze how the pattern of influence (shock) between the variable interest rate and a variable rate to variable inflation and to analyze how the pattern of influence (shock) between inflation, exchange rates, and interest rates on the export of fishery products Bali Province. Data analysis technique used is the analysis of Vector Auto Regression (VAR) with the help of Eviews 8.0 applications. Results of the analysis showed inflation variable significant negative effect on second lag on the export of fishery products in the province of Bali. Variable rate no significant effect on the export of fisheries in the province of Bali. Variable interest rates and significant negative berepengaruh the first lag and lag positively on both the export of fishery products in the province of Bali. The results of this research was supported by the impulse response analysis and analysis of variance decompositions that show that the proportion of the largest and most diverse on the variables affecting export of fisheries in the province of Bali.
Keywords: Exports, Inflation, Dollar Exchange Rates, Interest Rates, Vector Auto Regression, Impulse Response, Variance decompositions